Prescription of the rights derived from the contract reality according to the jurisprudence of the Council of State - González Vargas, Víctor Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The "reality contract" has generated various legal-procedural debates within the jurisdiction of contentious-administrative matters. One of them has been the application of the extinctive prescription on the rights that derive from the declaration of existence of the employment relationship, which has led the Second Section of the Council of State to unify its jurisprudence, in the sense of establishing, first, that the claim for these rights must be filed within 3 years following the termination of the contractual relationship; second, that if there are successive contracts, with interruptions of more than 30 business days, the interruption of continuity operates and, therefore, the prescription must be analyzed from the end dates of each of these contracts, taking into account the particularities of each case; third, that pension contributions are imprescriptible; and fourth, that the exception of extinctive prescription of the right must be resolved in the sentence and not previously. The objective of this article is to expose the different theses that were raised at the time on the application of the extinctive prescription in the "reality contract" and to show how this legal figure currently operates.